Chronic diaphragmatic hernia and axial skeletal anomalies in a cat – Case report (Research, Society and Development, 2023)
Diaphragmatic hernia and congenital anomalies of the axial skeleton are alterations frequently identified in domestic cats. The objective of this case report was to present the electrocardiographic, radiographic, and tomographic findings observed in a 5-year-old neutered domestic shorthair cat, with skeletal malformations simultaneously with chronic diaphragmatic hernia. The cat lived well until he was 10-years old, when he developed progressive respiratory compromise leading to death. To our knowledge, occurrence of combined diaphragmatic hernia and congenital skeletal anomalies in domestic cats is very rare.